ANALYSIS OF COAL QUALITY IMPROVEMENT USING CHEMICAL METHODS FOR MEETS STANDARDS OF CALORIFIC VALUE - Nahar, N; Ridwan, R; Irwan, I; Pardi, P (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACT As a country with relatively large coal resources and reserves, Indonesia will face challenges that are not easy in the future. The large amount of coal resources and reserves as well as the continuity of the coal mining industry cannot be ignored. Coal consumption in the world is expected to continue from time to time, especially in the Asian region. Lignite coal reserves account for around 48% of total coal reserves in the world, meanwhile in Asia lignite coal reserves reach 30%, while in Indonesia they reach 60% of total coal reserves. Although the amount of lignite coal consumed accounts for around 30% of total world coal production. The amount consumed in Asia accounts for only 10% of its total coal production. Especially in Indonesia, mining practices tend to tend to be higher quality bituminous and sub-bituminous coal which is more widely mined and produced because producing lignite coal is less economical and cannot meet market criteria. Thus, it can be predicted that what will remain in the future will be a large amount of lignite coal reserves that cannot be utilized. Because the opportunity to fill the potential of the coal market is still wide open, whether used directly as an energy source in power plants or exported abroad, promotion of the use of lignite coal must be made as early as possible as a very important issue for Indonesia. To improve the quality of lignite coal to coal whose quality is like that of anthracite coal so that it can be used, therefore it is necessary to have technology to improve the quality of lignite coal, so the Industrial Innovation Research research will improve the quality of coal using the stirring method by varying the influence of temperature and mixing time. coal, residual oil and kerosene can reduce the water content contained in low rank coal by the adsorption process. The research results show that operating conditions greatly influence the distribution of coal products. Relatively good operating conditions were obtained at a temperature of 200o C and a reaction time of 70 minutes with the results of: oil: 25 ml, water content: 0.668%, ash content: 11.883%, volatile matter: 30.122%, fixed carbon: 57.377%, and calorific value : 6581 Kcal/kg.Key words: Coal; Quality; Kerosene; Calorific Value; Enhancement